Controlled Anisotropic Growth of Co‐Fe‐P from Co‐Fe‐O Nanoparticles1. Issue 33 (26th June 2015) - Mendoza‐Garcia, Adriana; Zhu, Huiyuan; Yu, Yongsheng; Li, Qing; Zhou, Lin; Su, Dong; Kramer, Matthew J.; Sun, Shouheng
Abstract A facile approach to bimetallic phosphides, Co‐Fe‐P, by a high‐temperature (300 °C) reaction between Co‐Fe‐O nanoparticles and trioctylphosphine is presented. The growth of Co‐Fe‐P from the Co‐Fe‐O is anisotropic. As a result, Co‐Fe‐P nanorods (from the polyhedral Co‐Fe‐O nanoparticles) and sea‐urchin‐like Co‐Fe‐P (from the cubic Co‐Fe‐O nanoparticles) are synthesized with both the nanorod and the sea‐urchin‐arm dimensions controlled by Co/Fe ratios. The Co‐Fe‐P structure, especially the sea‐urchin‐like (Co0.54Fe0.46)2P, shows enhanced catalysis for the oxygen evolution reaction in KOH with its catalytic efficiency surpassing the commercial Ir catalyst. Our synthesis is simple and may be readily extended to the preparation of other multimetallic phosphides for important catalysis and energy storage applications.